Relationships between vertical jump and full squat power outputs with sprint times in U21 soccer players - Lopez-Segovia, M.; Marques, M. C.; van den Tillaar, R.; Gonzalez-Badillo, J. J. (Journal of Human Kinetics, 2011)
The aim of this study was to assess the relationship between power variables in the vertical jump and full squat with the sprint performance in soccer players. Fourteen under-21 soccer players were evaluated in two testing ssssions separated by 7 days. In the first testing session, vertical jump height in countermovement was assessed, and power output for both loaded countermovement jump (CMJL) and full squat (FS) exercises in two progressive load tests. The second testing session included sprinting at 10, 20, and 30m (T10, T20, T30, T10-20, T10-30, T20-30). Power variables obtained in the loaded vertical jump with 20kg and full squat exercise with 70kg showed significant relationships with all split times (r=-0.56/-0.79; p</=0.01/0.01). The results suggest that power produced either with vertical jump or full squat exercises is an important factor to explain short sprint performance in soccer players. These findings might suggest that certain levels of neuromuscular activation are more related with sprint performance reflecting the greater suitability of loads against others for the improvement of short sprint ability in under-21 soccer players.